Population growth of Daphnia sp. with various types of organic fertilizer - Rasman, Rasman; Patang, Patang; Amirah, Amirah (Nekton, 2024)
The Daphnia sp. population can be increased using various types of organic fertilizers. This study aimed to analyze the effect of organic fertilizer vermicompost, quail feces, and Black Soldier Fly (BSF) larvae compost on maintenance media on the growth of Daphnia sp. and identify the best dose. This research is an experimental study with a completely randomized design (CRD) with treatment K (control or no organic fertilizer), treatment A (addition of vermicompost organic fertilizer 2.4 g/l), treatment B (addition of quail feces organic fertilizer 2.4 g/l), treatment C (addition of fly larvae compost organic fertilizer 2.4 g/l). Water quality variables (temperatur, pH, dissolved oxygen (DO), color, and odor). The data were analyzed using Analysis of Variance (ANOVA). The data were analyzed using SPSS 22. The results of this study showed that the provision of organic fertilizer through the maintenance media had an effect (P <0.05) on the growth of Daphnia sp. The highest population was in treatment A (Quail Feces dose of 2.4 g / L) as many as 353 tails and the lowest in treatment K (No Dose) as many as 132 tails. The results of the water quality analysis of the morning temperatur were in the range–26-28ºC. afternoon temperatur was obtained 27-28ºC, then for morning pH ranged from 7.1-7.5 and afternoon pH obtained 7.3-7.6 while the average DO obtained 6.8 mg/L. The best dose in this study was treatment A with organic fertilizer 2.4 g/l.